Electronic Word of Mouth, Customer Engagement, and Purchase Behavior in Online Food Delivery - Laksono, Ahnif Jusmansyah; Munandar, Jono Mintarto; Nurhadryani, Yani (Indonesian Journal of Business and Entrepreneurship, 2026)
Background: Digital technology has transformed consumer behavior regarding online food ordering. The rapid growth of online food delivery services has intensified competition, making electronic word-of-mouth a critical factor influencing consumer interest and decision-making. Purpose: This study aims to examine the influence of eWOM usefulness and credibility on eWOM adoption and the subsequent effects of adoption on customer engagement, purchase intention, and purchase decisions in online food delivery services. Design/methodology/approach: Data were collected from 230 respondents aged 18 and above residing in Greater Jabodetabek who used online food delivery services and engaged with social media. The data were analyzed using descriptive statistics and Partial Least Squares structural equation modeling (PLS-SEM) with SmartPLS. Findings/Results: eWOM usefulness and credibility both positively influenced eWOM adoption, with coefficients of 0.41 and 0.43 respectively. eWOM adoption directly drives customer engagement and purchase intention, with coefficients of 0.53 and purchase decisions with coefficients of 0.67, 0.53, and 0.40, respectively. Furthermore, customer engagement directly strengthens purchase intention, with a coefficient of 0.24. Purchase intention directly enhanced purchase decisions, with a coefficient of 0.42. These results indicate that credibility has a slightly stronger effect on adoption than usefulness, highlighting the importance of trustworthy content in social media. For online food delivery platforms, enhancing the credibility and perceived usefulness of user reviews can effectively engage consumers, strengthen purchase intentions, and ultimately drive actual purchasing behavior. Conclusion: This study confirms that credible and useful eWOM reviews play a crucial role in driving consumer information adoption, fostering engagement, strengthening purchase intention, and enhancing purchasing behavior. Originality/value (State of the art): This study contributes to the literature by extending the applicability of the information adoption model (IAM) to the context of Indonesia’s online food delivery services. It also provides practical insights for platform managers to enhance review credibility and develop effective consumer engagement strategies in digital environments. Keywords: electronic word of mouth, customer engagement, purchase decision, purchase intention, online food delivery